Planowanie i budżetowanie projektów informatycznych w banku - Kowalczyk, Mirosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of this paper is to present issues concerning planning and budgeting IT projects in bank with emphasis on possible methods and tools. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 155-163